Flavin and deazaflavin biosynthesis in mycobacteria: relevance to physiology, implications for drug discovery, MR-1 antigenicity, and vaccine development - Oketade, Nurudeen; Chengalroyen, Melissa D.; Kain, Dylan; Lewinsohn, David M.; Dobos, Karen M. (Frontiers in Immunology, 2026)
Flavin and deazaflavin biosynthesis are highly conserved pathways in mycobacteria, including in Mycobacterium tuberculosis (M.tb). Flavin biosynthesis on one hand is required to produce FMN and FAD, two essential cofactors required to support the flavin intensive lifestyle of mycobacteria. Deazaflavin biosynthesis on the other hand provides F420, an important cofactor used by mycobacteria to curtail antimicrobial and immunological stressors. Given these crucial roles for mycobacterial survival and virulence, these connected pathways have been a recent focus of drug discovery efforts. In addition to providing these important cofactors, studies have shown that the intermediates of this pathway are required to produce metabolic antigens presented by the MHC class I related protein (MR1) molecule in mycobacteria. T cells restricted by the MR1 molecule, which includes Mucosal-associated invariant T cells (MAITs), have also been shown to play a key role during M.tb infection. These findings have made MR1 restricted T cells a prime target for vaccine development. In this review, we focus on what is known about flavin and deazaflavin synthesis pathways in M.tb and other mycobacteria and the distinct features in these species. We also cover the role of these pathways in the physiology of mycobacteria, as well as the status of small molecule inhibitors targeting this pathway. We discuss the current understanding of MR1 immunology in M.tb infection, based on studies in both animal models and humans. Additionally, we highlight recent findings on the diverse repertoire of MR1 T cell receptors that expand during infection and the current status of the MR1 ligandome. Most importantly, we discuss current gaps in understanding the importance of these pathways and explore how this knowledge could drive the development of therapeutics for mycobacterial diseases by targeting these pathways and protective MR1-restricted T cell responses.